2020
DOI: 10.1111/1440-1681.13284
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular tumour necrosis factor ligand related molecule 1 A links disease progression of proliferative diabetic retinopathy after primary vitrectomy

Abstract: Tumour necrosis factor ligand related molecule 1 A (TL1A), a member of tumour necrosis factor superfamily, has been identified as a crucial regulator for vascular homeostasis and inflammation. However, the function of TL1A in diabetic retinopathy (DR) is largely unknown. This study aims to examine levels of TL1A in serum and intraocular fluid in patients with proliferative diabetic retinopathy (PDR), and to explore the correlation of intraocular TL1A with the prognosis of PDR progression after primary vitrecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…TNF- α is a small molecule protein secreted by macrophages, and its expression is regulated by the NF- κ B signaling pathway. Wang et al showed that the levels of TNF- α in the tears of DR patients are proportional to the severity of the disease [ 31 ]. IL-1 β is mainly produced by macrophages, which promotes the release of neutrophils from bone marrow and induces monocytes to release lysosomal enzymes locally, resulting in local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF- α is a small molecule protein secreted by macrophages, and its expression is regulated by the NF- κ B signaling pathway. Wang et al showed that the levels of TNF- α in the tears of DR patients are proportional to the severity of the disease [ 31 ]. IL-1 β is mainly produced by macrophages, which promotes the release of neutrophils from bone marrow and induces monocytes to release lysosomal enzymes locally, resulting in local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors, such as duration of diabetes, poor metabolic control, and onset of diabetes before puberty [28] and levels of inflammatory cytokines after primary vitrectomy [29], have been proven to be related to the progression of DR. In our study, multivariate logistic regression analysis showed that the AH level of VEGF 165 b/ VEGF ratio was an independent negative factor in the progression of DR, which suggests that a lower VEGF 165 b/VEGF ratio may have predictive value in determining diabetic patients at risk for DR progression.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is one of the most destructive microvascular complications of diabetes mellitus. Intraocular neovascularization and diabetic macular edema (DME) are two major clinicopathologic features during the development and progression of DR [ 1 , 2 ]. The occurrence of neovascularization is closely related to the duration of diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%